2015
DOI: 10.1038/ncomms7606
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hippocampal neurogenesis contributes to epilepsy and associated cognitive decline

Abstract: Acute seizures after a severe brain insult can often lead to epilepsy and cognitive impairment. Aberrant hippocampal neurogenesis follows the insult but the role of adult-generated neurons in the development of chronic seizures or associated cognitive deficits remains to be determined. Here we show that ablation of adult neurogenesis prior to pilocarpine-induced acute seizures in mice leads to a reduction in chronic seizure frequency. We also show that ablation of neurogenesis normalizes epilepsy-associated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
351
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 373 publications
(404 citation statements)
references
References 57 publications
19
351
5
8
Order By: Relevance
“…It is currently unknown whether these anomalies by themselves are adequate to induce spontaneous seizures (48). Nonetheless, their involvement in manifestations of spontaneous seizures after SE has been well documented (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unknown whether these anomalies by themselves are adequate to induce spontaneous seizures (48). Nonetheless, their involvement in manifestations of spontaneous seizures after SE has been well documented (49)(50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…One in particular concerns the impact of antineurogenic treatments on sprouting: specifically, while blocking neurogenesis with methylazoxymethanol acetate (MAM) proved effective at reducing sprouting (in a study by Liu and colleagues [8]), recent studies using transgenic thymidine-kinase and diphtheria toxin-mediated cellablation strategies found no impact on eliminating juvenile and newborn granule cells on mossy fiber sprouting (9,10). Future studies will be needed to resolve these discrepancies.…”
Section: Mossy Fiber Sprouting In the Epileptic Brain: Taking On The mentioning
confidence: 99%
“…Seizure activity can induce robust generation of ectopically localized granule cells in the adult hippocampus. Jenny Hsieh (UT Southwestern Medical Center, Dallas, USA) showed that ablation of adult neurogenesis before pilocarpineinduced seizures in the nestin-TK transgenic mouse line can lead to improved cognitive function and a significant reduction of chronic seizure frequency (Cho et al, 2015). She further presented unpublished data using a chemogenetic approach to determine whether silencing adult-born neuronal activity can result in a reduction of seizure frequency.…”
Section: Targeting Adult Neurogenesis To Promote Repair and Prevent Dmentioning
confidence: 99%